Human T-cell clones from autoimmune thyroid glands: specific recognition of autologous thyroid cells. - Londei, M; Bottazzo, G; Feldmann, M (1985)
The thyroid glands of patients with autoimmune diseases such as Graves' disease and certain forms of goiter contain infiltrating activated T lymphocytes and, unlike cells of normal glands, the epithelial follicular cells strongly express histocompatibility antigens of the HLA-DR type. In a study of such autoimmune disorders, the infiltrating T cells from the thyroid glands of two patients with Graves' disease were cloned in mitogen-free interleukin-2 (T-cell growth factor). The clones were expanded and their specificity was tested. Three types of clones were found. One group, of T4 phenotype, specifically recognized autologous thyroid cells. Another, also of T4 phenotype, recognized autologous thyroid or blood cells and thus responded positively in the autologous mixed lymphocyte reaction. Other clones derived from cells that were activated in vivo were of no known specificity. These clones provide a model of a human autoimmune disease and their analysis should clarify mechanisms of pathogenesis and provide clues to abrogating these undesirable immune responses.